SOIL FAUNAL DIVERSITY AS A BIOINDICATOR OF SOIL HEALTH ACROSS DIFFERENT LAND-USE TYPES - Juliano, Gian; Mahardika, Rabbirl Yarham; Hidayah, Anggraeni Nur; Mardhiah, Mira; Alayya, Nahdlia Putri; Prayudi, Haikal Caesa; Putri, Elsa Kumala; Sulistiyawati, Dita; Dirman; Sagala, Mariyetha; Gusviani, Nisa Azzahra (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2026)
This study examines soil mesofauna and macrofauna as bioindicators of soil health and ecological integrity across three land-use systems: oil palm plantations, open lands, and bamboo forests. Land-use change increasingly threatens soil biodiversity and ecosystem functioning in tropical regions, where soil organisms are key to nutrient cycling, aggregation, and ecological resilience. Understanding how land use influences soil faunal communities is crucial for assessing belowground integrity. Despite their critical ecological roles, soil faunal indicators are rarely integrated into soil health assessments in tropical systems. Addressing this gap, this study compares soil mesofauna and macrofauna diversity across contrasting land uses to establish their potential as reliable bioindicators. Soil samples were collected from the surface layer (0–10 cm) using standardized coring under uniform topography, soil type, and climate. Systematic random sampling was applied, with mesofauna extracted using Berlese-Tullgren funnels and macrofauna extracted by manual hand-sorting following the TSBF method. Specimens were identified to the order level. Shannon-Wiener analysis showed that bamboo forests supported the most complex and functionally rich communities (mesofauna H′ = 1.498; macrofauna H′ = 0.309), followed by oil palm plantations and open lands. Acari and Collembola were dominant mesofauna sensitive to habitat quality, while Formicidae and Diplopoda reflected higher trophic and structural roles. Open lands exhibited low diversity and dominance of stress-tolerant taxa, indicating reduced ecological function. The integrated assessment of mesofauna and macrofauna provides a robust framework for evaluating soil health, highlighting vegetation complexity as a driver of nutrient cycling, aggregation, and microbial activity.